Rewrite the equation using function notation. Graph the function and show the intercepts.

3x + 3y = 6

x + y = 2

y = 2-x

Then you can get f(x)=2-x

An x-intercept is a point on the graph where y is zero, and a y-intercept is a point on the graph where x is zero.

So, for x-intercept: 0 = 2-x. We can get x = 2. Point(2,0)

for y-intercept: y = 2-x = 2-0 = 2. Point(0,2)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up